Optimization of pathogen detection in abscess specimens: a 6-year retrospective study - Qiangsheng Feng; Xiaoqing Ha; Wenyun Guo; Yuan Xing; Juling zhang; Chenchen Zhang; Qi Zhang; Yuejuan Song (European Journal of Medical Research)
Abstract Background This study aimed to evaluate the impact of optimized diagnostic protocols on pathogen detection rates in abscess specimens. Methods Our retrospective study analyzed 1,297 abscess specimens collected between 2018 and 2024 using an enhanced diagnostic protocol combining four key methodologies: routine aerobic/anaerobic culture, gram-stain microscopy, acid-fast bacilli staining, and blood culture bottle enrichment techniques. Results The implementation of optimized diagnostic protocols significantly enhanced pathogen detection efficacy (P < 0.001, χ = 9.663), achieving an overall positivity rate of 81.9% (1,062/1,297)—a 20.1 percentage point improvement over conventional methods. Among culture-positive specimens, polymicrobial infections were identified in 27.6% of cases (293/1,062). A total of 1,651 microbial isolates were recovered, dominated by gram-negative bacteria (50.6%, 836/1,651) with Escherichia coli (55.0%), Klebsiella pneumoniae (23.0%), and Acinetobacter baumannii (4.0%) as predominant species. Gram-positive cocci accounted for 33.7% (557/1,651), primarily Streptococcus spp. (45.0%), Staphylococcus aureus (19.0%), and Enterococcus faecium (6.0%). Enhanced methodology detected 261 additional pathogens (20.1% of total yield), including anaerobes (33.7%), smear-positive organisms (32.2%), acid-fast bacilli (6.9%), and Brucella melitensis (1.5%). Anatomic distribution analysis revealed perianal abscesses (358 cases, 407 isolates) predominantly associated with E. coli (51.8%), K. pneumoniae (14.7%), and Streptococcus spp. (15.7%), followed by maxillofacial infections (244 cases, 297 isolates; 18.0%). Other significant sites included abdominal abscesses/peritonitis (17.0%), hepatic abscesses (5.2%), and Periappendicular abscess (5.5%). Conclusions Systematic optimization of diagnostic protocols significantly enhanced pathogen detection in abscess specimens, demonstrating substantial clinical utility for infectious disease management. These findings support the adoption of comprehensive, standardized approaches for abscess specimen processing.